Evaluation of a regional nerve block with an experimental formulation of encapsulated lidocaine in sheep. (November 2020) - Militana, Erika A.; Campoy, Luis; Martin-Flores, Manuel; Gleed, Robin D.
Abstract: Objective: To compare the duration of nociceptive and proprioceptive blockade from an experimental encapsulated lidocaine preparation with that of conventional lidocaine. Study design: Prospective, blinded, randomly assigned, crossover study. Animals: A total of six adult Dorset ewes, American Society of Anesthesiologists physical status I or II, weighing 60.4 ± 18.0 kg (mean ± standard deviation). Methods: Under general anesthesia and guided by electrolocation, the common peroneal nerve was blocked unilaterally with encapsulated lidocaine (0.1 mL kg –1, 200 mg mL –1 ) or conventional lidocaine hydrochloride (0.1 mL kg –1, 20 mg mL –1 ). Each sheep was administered both treatments with an interval of 2 weeks between treatments. Nociception and proprioception were scored (scales of 0–3) before anesthesia, at 0.5, 1, 2, 4, 8, 12, 16, 20 and 24 hours after completion of local anesthetic injection, and every 12 hours thereafter for 9 days. Nociceptive and proprioceptive blockade ended the first time each score reached '0'; maximum blockade duration was considered and recorded to be the time point immediately prior to this end point. Significance of differences between treatments for duration of blockade was tested with the Wilcoxon rank-sum test. Effects of time and treatment on nociceptive and proprioceptive blockade were evaluated with mixed-effect models. Significance was set at p < 0.05. Results: Compared with conventional lidocaine, nociceptive blockade lasted 88 hours longer with encapsulated lidocaine ( p = 0.008), and proprioceptive blockade lasted 6 hours longer ( p = 0.03). Significant effects of time ( p < 0.0001), treatment ( p = 0.0435) and treatment∗time ( p < 0.0001) were observed for nociception. Significant effects of time ( p < 0.0001) and treatment∗time ( p = 0.0058) were observed for proprioception. Conclusion: Encapsulated lidocaine produced nociceptive blockade with a duration substantially longer than conventional lidocaine. Clinical relevance: Sustained-release encapsulated lidocaine alleviates pain and may minimize systemic analgesic use.